Zakat: A Viable Islamic Social Finance Instrument to Reduce Child Labour in Malaysia - Yusuff Jelili, Amuda; Nik Ahmad, Kamal; Ashgar Ali, Ali Muhamed; Azizah, Mohd; Marhanum, Che Mohd Salleh (2016)
Notwithstanding the commendable efforts of the Malaysian government of providing some social safety nets and cash transfers to its citizens, it is worrisome that some Malaysian children are still subjected to child labour. Child labour is a global plight due to poverty, culture, laziness, and corruption, among others. Islam as a religion not only abhors this practice by spelling out the roles of parents and the government in tackling this social menace, but also recommends possible solutions. As such, Malaysia being a Muslim majority country and with a viable institutional arrangements that capture Islamic social finance application and implementation, Zakat is arguably a potentially effective tool to curb child labour. The study focuses on examining how zakat funds can be productively utilised through the use of a portion of zakat proceeds in the development of working children. Th is research examines how zakat can be used for child labour human development economically, educationally, medically, religiously, and socially in Malaysia. The study applied both qualitative and quantitative methods throughout the discussion. Finally, useful solutions to outstanding problems are suggested in the findings.